A Drug‐Free Tumor Therapy Strategy: Cancer‐Cell‐Targeting Calcification. (17th March 2016) - Zhao, Ruibo; Wang, Ben; Yang, Xinyan; Xiao, Yun; Wang, Xiaoyu; Shao, Changyu; Tang, Ruikang
Abstract: Herein, we propose a drug‐free approach to cancer therapy that involves cancer cell targeting calcification (CCTC). Several types of cancer cells, such as HeLa cells, characterized by folate receptor (FR) overexpression, can selectively adsorb folate (FA) molecules and then concentrate Ca 2+ locally to induce specific cell calcification. The resultant calcium mineral encapsulates the cancer cells, inducing their death, and in vivo assessments confirm that CCTC treatment can efficiently inhibit tumor growth and metastasis without damaging normal cells compared with conventional chemotherapy. Accordingly, CCTC remarkably improve the survival rate of tumor mice. Notably, both FA and calcium ions are essential ingredients in human metabolism, which means that CCTC is a successful drug‐free method for tumor therapy. This achievement may further represent an alternative cancer therapy characterized by selective calcification‐based substitution of sclerosis for tumor disease.